Novel application potential of cinaciguat in the treatment of mixed hyperlipidemia through targeting PTL/NPC1L1 and alleviating intestinal microbiota dysbiosis and metabolic disorders - Ang Jia; Hongfei Jiang; Wenjing Liu; Pengwei Chen; Qi Xu; Renshuai Zhang; Jufeng Sun (Elsevier, 2023)
Mixed hyperlipidemia, characterized by high levels of triglycerides and cholesterol, is a key risk factor leading to atherosclerosis and other cardiovascular diseases. Existing clinical drugs usually only work on a single indicator, decreasing either triglyceride or cholesterol levels. Developing dual-acting agents that reduce both triglycerides and cholesterol remains a great challenge. Pancreatic triglyceride lipase (PTL) and Niemann-Pick C1-like 1 (NPC1L1) have been identified as crucial proteins in the transport of triglycerides and cholesterol. Here, cinaciguat, a known agent used in the treatment of acute decompensated heart failure, was identified as a potent dual inhibitor targeting PTL and NPC1L1. We presented in vitro evidence from surface plasmon resonance analysis that cinaciguat interacted with PTL and NPC1L1. Furthermore, cinaciguat exhibited potent PTL-inhibition activity. Fluorescence-labeled cholesterol uptake analysis and confocal imaging showed that cinaciguat effectively inhibited cholesterol uptake. In vivo evaluation showed that cinaciguat significantly reduced the plasma levels of triglycerides and cholesterol, and effectively alleviated high-fat diet-induced intestinal microbiota dysbiosis and metabolic disorders. These results collectively suggest that cinaciguat has the potential to be further developed for the therapy of mixed hyperlipidemia.